Characterization of Layer Number of Two-Dimensional Transition Metal Diselenide Semiconducting Devices Using Si-Peak Analysis - Xian Zhang (Advances in Materials Science and Engineering)
Atomically thin materials such as semiconducting transition metal diselenide materials, like molybdenum diselenide (MoSe2) and tungsten diselenide (WSe2), have received intensive interests in recent years due to their unique electronic structure, bandgap engineering, ambipolar behavior, and optical properties and have motivated investigations for the next-generation semiconducting electronic devices. In this work, we show a nondestructive method of characterizing the layer number of two-dimensional (2-D) MoSe2 and WSe2 including single- and few-layer materials by Raman spectroscopy. The related photoluminescence properties are also studied as a reference. Although Raman spectroscopy is a powerful tool for determining the layer number of 2-D materials such as graphene and molybdenum disulfide (MoS2), there have been difficulties in precisely characterizing the layer number for MoSe2 and WSe2 by Raman spectroscopy due to the uncertain shifts during the Raman measurement process and the lack of multiple separated Raman peaks in MoSe2 and WSe2 for referencing. We then compared the normalized Si peak with MoSe2 and WSe2 and successfully identified the layer number of MoSe2 and WSe2. Similar to graphene and MoS2, the sample layer number is found to modify their optical properties up to 4 layers.